2007
DOI: 10.1080/00365590701226036
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy and long-term compliance/treatment failure of the α1 blocker naftopidil for patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia

Abstract: There were significant improvements in IPSS and urinary flow rate with naftopidil although it is unknown whether these improvements were significantly larger than the placebo effect as the study was non-randomized. However, only 19% of patients were known to have continued with the same medication for 4 years in real-life clinical practice. Patients who have a large prostate at baseline and a severe IPSS at 12 weeks after treatment are more likely to have treatment failure, although a prospective study is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 21 publications
7
51
2
Order By: Relevance
“…On the other hand, PV at baseline is a predictive factor for the efficacy of α1-blockers [14,18,19]. PV was a predictive factor of the efficacy of naftopidil only in the 75 mg/day TID group, not in the 75 mg OD group in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, PV at baseline is a predictive factor for the efficacy of α1-blockers [14,18,19]. PV was a predictive factor of the efficacy of naftopidil only in the 75 mg/day TID group, not in the 75 mg OD group in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…20 Several static and dynamic variables to predict treatment failure and conversion to surgery of a1-blockers have been reported. 5,8,13,14,21 De la Rosette showed that static variables, such as a severe IPSS, poor Qmax, an enlarged prostate and BOO on pressureflow study, were risk factors for treatment failure. 13 They also showed that a higher PSA value and larger PV resulted in a greater risk of BPH-related invasive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that patients who had a large PV at baseline, as well as severe IPSS at 12 weeks after treatment, were more likely to have treatment failure during a 4-year follow-up period. 8 However, the study was carried out as a retrospective study using naftopidil, which has a threefold higher affinity for a1D than for the a1A subtype and is only available in Japan. 12 Thus, in the present study, we prospectively evaluated what percentage of patients dropped out during a 5-year follow-up period after administration of tamsulosin, which has a threefold higher affinity for a1A than for the a1D subtype and is universally available, and the reasons why they terminated medication, including patients who were lost to follow up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical treatment is the first-line option for bothersome LUTS/BPH. In case of failure of medical management [2,3] or complications due to BPH, surgical management is recommended [1]. Transurethral resection of the prostate (TURP) remains the gold standard to which all other therapies should be compared [4], but is associated to complications including intra- and postoperative bleeding, TURP syndrome and sexual disorders such as retrograde ejaculation and erectile dysfunction [1,5,6].…”
Section: Introductionmentioning
confidence: 99%